Kompetensi Pedagogik Guru dalam Pembelajaran PAI Berdasarkan Kemampuan Berpikir Tingkat Tinggi (HOTS) - Iis Suryatini; Rohman Heryana; Mochammad Ramdan Samadi; Saepudin (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
This study examines the efforts and programmes designed to enhance the pedagogic competence of Islamic Education (PAI) teachers through the integration of Higher Order Thinking Skills (HOTS). The research follows a qualitative descriptive methodology, focusing on literature review as the primary means of data collection. The study systematically explores the significance of continuous professional development, including training, mentoring, and collaborative learning environments, in improving teachers' abilities to foster critical, analytical, and creative thinking among students. Additionally, it analyses the role of technology in supporting pedagogic practices and emphasises the need for schools to adopt policies that promote active learning and critical assessment methods. The findings suggest that by enhancing the pedagogic competence of PAI teachers, students will be better prepared to face the challenges of modern education, leading to improved learning outcomes. This research underscores the urgency of aligning teacher competencies with contemporary educational standards, particularly through the effective integration of HOTS in classroom practices.